Upaya Guru PAI dalam Meningkatkan Hasil Belajar Peserta Didik pada Materi Kisah Hijrah Nabi Muhammad SAW ke Madinah Melalui Metode Group Investigation pada Siswa Kelas IV SD 11 Kota Bengkulu Tahun Ajaran 2024/2025 - Muhammad Nuh (GHAITSA : Islamic Education Journal, 2025)
This study aims to improve the strategy and quality of learning in Islamic Religious Education subjects, especially in the material telling the story of the Prophet Muhammad's migration to Medina. Students continue to be given guidance in telling the story of the Prophet Muhammad's migration to Medina. Students are able to tell the story of the Prophet Muhammad's migration to Medina. Fostering enthusiasm in students in telling the story of the Prophet Muhammad's migration to Medina. This research is a classroom action research which is divided into two cycles and begins with a pre-cycle. Each cycle consists of planning, implementing actions, observation, evaluation, and reflection. The research was conducted on grade IV students at SD 11 Kota Bengkulu in the 2024/2025 academic year. The results of the study The teacher's efforts to improve the learning outcomes of Islamic Religious Education on the material of the Prophet Muhammad's migration to Medina through the group investigation method for students of SD 11 Kota Bengkulu went quite well. The learning activity process carried out was quite good according to plan and the teaching and learning process went smoothly and there was an increase. Student activity in the teaching and learning process is quite good in the percentage of observation results to students from the first cycle 68.75 and the second cycle 96.67. The results of the formative test scores increased, which in cycle I averaged 6.67 and in cycle II averaged 8.13.